2022
DOI: 10.1039/d2an01227h
|View full text |Cite
|
Sign up to set email alerts
|

A headspace collection chamber for whole body volatilomics

Abstract: The human body secretes a complex blend of volatile organic compounds (VOCs) via the skin, breath and bodily fluids, the study of which can provide valuable insight into the physiological...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 110 publications
5
19
0
Order By: Relevance
“…We next leveraged our previous analyses of human whole body headspace 48 to target the primary chemical constituents of human whole body odor, confirming the identity of 40 known VOCs detected in whole body odor in this semi-field dataset (Fig. S12).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…We next leveraged our previous analyses of human whole body headspace 48 to target the primary chemical constituents of human whole body odor, confirming the identity of 40 known VOCs detected in whole body odor in this semi-field dataset (Fig. S12).…”
Section: Resultssupporting
confidence: 66%
“…The human body emits hundreds of volatile organic compounds (VOCs) in exhaled breath and skin emissions 64 , and our prior research has demonstrated considerable heterogeneity in the chemical complexity of whole body emissions between humans 48 . This natural variation in the types and abundances of VOCs emitted by the human body has long been hypothesized as a key factor driving mosquito host preference 65 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in chamber experiments where the human subjects were controlled for bathing and clothing, divergent findings have been reported regarding baseline emissions for ozonolysis products. Some studies reported low baseline emissions, ,,, while some others suggested substantially higher levels . In real-world scenarios, the soiling conditions of skin and clothing can differ by occupants, adding extra variability to the apparent baseline emissions.…”
Section: Resultsmentioning
confidence: 99%